2022
DOI: 10.1007/s10660-022-09591-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimal contract design for live streaming shopping in a manufacturer–retailer–streamer supply chain

Abstract: This study considers a manufacturer–retailer–streamer supply chain, in which the retailer first purchases products from a manufacturer and then sells them to consumers through a streamer. In the live streaming context, the retailer usually cooperates with the streamer by providing three different contracts: only a commission of the sale (OC), only a fixed fee (OF), and a commission of the sale and fixed fee (CF). Therefore, this study develops a theoretical model to investigate the effects of these three contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Xu et al [23] studied the manufacturer's sales modes of products directly or indirectly through the platform that provides live-streaming functionality. He et al [24] investigated the optimal contract design for live-streaming shopping by designing three cooperation methods between retailers and live streamers. In addition, some scholars have focused on live-streaming marketing strategies based on the introduction of live-streaming channels [25].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al [23] studied the manufacturer's sales modes of products directly or indirectly through the platform that provides live-streaming functionality. He et al [24] investigated the optimal contract design for live-streaming shopping by designing three cooperation methods between retailers and live streamers. In addition, some scholars have focused on live-streaming marketing strategies based on the introduction of live-streaming channels [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the high pit fees are eroding the profts of enterprises, as they need to pay the pit fees in advance, and it is unknown whether the live streamers can achieve a certain number of sales, which means that the risk is entirely borne by the enterprise. Terefore, to better expand LCs, live streamers should control their pit fees and collaborate with brand owners [24].…”
Section: Te Brand Owner and Live Streamer Form A Coalition Blmentioning
confidence: 99%
“…Fan et al [ 10 ] explored the live commerce spillover effect on manufacture's original channel with Stackelberg game and found that the existence of live commerce spillover effect increases manufacture's profit while it cuts down streamer's. Optimal transaction mechanism between retailer and streamer among only commission fee, only fixed fee and both commission and fixed fee was investigated by He et al [ 15 ]. Wang et al [ 34 ] discussed the distribution contract selection between supplier and platform in the context of live streaming e-commerce and put forward the suggestion on the selection of streamer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The information value and entertainment value provided by streamers’ marketing effort have a positive effect on consumers' purchase intention [ 7 , 12 , 23 , 37 ]. We use to denote the marketing effort of the streamer, and the cost of marketing effort satisfies quadratic function which is widely used in previous research [ 15 ]. The demand function is derived from consumer behavior and the utility is positive correlation with marketing effort and negative correlation with product price.…”
Section: Model Setupmentioning
confidence: 99%
“…Fan, Wang & Song [8] argued that the live streaming service of streamers affects both the sales of traditional channel manufacturers as well as the return rate when selling products live. He, Chen & Mu [9] looked at three modes for inviting streamers to sell commodities: commission-only, fixed-fee, and a combination of both. The study indicated retailers prefer to work with streamers with high sales capacity in a pure commission mode.…”
Section: Literature Reviewmentioning
confidence: 99%